Емоційні оказіоналізми в художній прозі Михайла Стельмаха - Попова, О.І. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
Здійснено лінгвостилістичний аналіз оказіоналізмів Михайла Стельмаха. З’ясовано стилістичний потенціал виявлених оказіоналізмів та особливості їх використання з метою стилізації розмовності та оновлення й збагачення образних ресурсів художніх творів письменника. Осуществлено лингвостилистический анализ окказионализмов Михаила Стельмаха. Выяснено стилистический потенциал окказионализмов и особенности их использования с целью стилизации разговорности и обогащения образных ресурсов художественных произведений писателя. In the article the linguo-stulistic analysis, clucked in the fiction prose texts of Mykhailo Stel’makh is implemented. This article also contains the out view of the stylistic potential of the individual and author’s neologisms and the peculiarities of their use when styling the colloquial style speech and refreshing and enriching the image resources of the colloquial style speech and refreshing and enriching the image resources of the author’s works.